AC016405.3 functions as an oncogenic long non‐coding RNA by regulating ERBB3 via sponging miR‐22‐3p in breast cancer. Issue 9 (17th August 2021) - Wei, Min; Wang, Jie; He, Qi; Liu, Lei; Wang, Zhiwei
Abstract: Background: Increasing studies reported that long non‐coding RNAs are involved in regulating breast cancer (BRCA) progression. However, the specific roles and mechanisms of lncRNAs in BRCA remain largely unknown. Here, we sought to explore the functions and mechanisms of AC016405.3 in BRCA progression. Methods: Bioinformatic analysis for AC016405.3, miR‐22‐3p, and ERBB3 were performed on starBase. The expressions of AC016405.3, miR‐22‐3p, and ERBB3 were examined by RT‐qPCR. The functions of AC016405.3 on the proliferation, migration, and invasion of cells were evaluated by conducting CCK‐8, colony formation, wound‐healing, and Transwell assays. The subcellular distribution of AC016405.3 in BRCA cells was identified by performing fluorescence in situ hybridization (FISH) and subcellular fractionation techniques. Dual‐luciferase assay was applied to validate the interactions of miR‐22‐3p with AC016405.3 or ERBB3. The interaction between ERBB3 and miR‐22‐3p was also tested by Anti‐Ago2 RNA immunoprecipitation (RIP) assay. Results: The results showed that AC016405.3 is highly expressed in BRCA tissues as well as cells and positively correlated with poor prognosis in BRCA patients. Silencing AC016405.3 obviously repressed the malignant behaviors of BRCA cells. Mechanistically, AC016405.3 functioned as a competing endogenous RNA (ceRNA) for miR‐22‐3p in the cytoplasm and sponged miR‐22‐3p to release its suppression of ERBB3. Rescue experiments revealed that the suppression role induced by AC016405.3 depletion on malignant behaviors of BRCA cells could be obviously counter by inhibiting miR‐22‐3p or overexpressing ERBB3. Conclusion: AC016405.3 promotes BRCA progression by the derepression of ERBB3 via sponging miR‐22‐3p, which may represent a potential target for BRCA treatment. Abstract : AC016405.3 is involved in BRCA progression by up‐regulating ERBB3 expression via miR‐22‐3p. BRAC cells (MCF7 and ZR7530) were co‐transfected si‐AC016405.3 with empty vector (EV) or ERBB3 overexpression vector (ERBB3). The proliferation of BRAC cells from different groups was examined by (A) CCK‐8 and (B) colony formation assays. (C) Wound‐healing assay assessed the migration ability of BRAC cells from different groups. (D) Transwell assay evaluated both the migration and invasion of BRAC cells from different groups. (E) A schematic diagram exhibited the proposed mechanism that cytoplasmic AC016405.3 sponges miR‐22‐3p to promote ERBB3 expression thus contributes to BRCA progression. Note: ** p  < 0.01 and *** p  < 0.005. Scale bar = 100μm.